ENSINO MÉDIO E EDUCAÇÃO PROFISSIONAL NO TEMPO PRESENTE: PARA ALÉM DA DUALIDADE ESCOLAR - Claudia Pereira de Pádua Sabia; Silvio Cesar Nunes Militão (Universidade do Oeste Paulista, 2011)
The survey was conducted by standard procedures for survey and analysis of literature and documents, and aimed to analyze the main changes experienced by high school and vocational education under the approval of the legal order in force: the 1988 Federal Constitution, Law of Directives and Bases of National Education - Law no. 9.394/96 and Decree no. 2.208/97, repealed by Decree no. 5.154/04. Part of a brief historical overview of the emergence and organization of schooling and such, following examines the main changes experienced by high school and vocational education brought about by the current set of laws, according to the guidelines of reform and rationalization of the state, from the hegemonic years 1990. The survey results indicate that, to date, we have not yet overcome the historical duality that has prevailed in the final stage of basic education. Concludes that the "Innovative School" may be a viable way to integrate high school and vocational education.